ChemInform Abstract: Highly Enantioselective Ring‐Opening Reactions of Aziridines with Indole and Its Application in the Building of C3‐Halogenated Pyrroloindolines. Issue 19 (May 2015) - Yang, Dongxu; Wang, Linqing; Han, Fengxia; Li, Dan; Zhao, Depeng; Cao, Yiming; Ma, Yunxia; Kong, Weidong; Sun, Quantao; Wang, Rui
Abstract: A magnesium‐catalyzed asymmetric ring‐opening reaction of aziridine with indole is realized by employing commercially available chiral ligands.